2015
DOI: 10.1152/ajpheart.00834.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a myosin regulatory light chain mutation K104E on actin-myosin interactions

Abstract: J. Effect of a myosin regulatory light chain mutation K104E on actin-myosin interactions. Am J Physiol Heart Circ Physiol 308: H1248 -H1257, 2015. First published March 13, 2015; doi:10.1152/ajpheart.00834.2014 is the most common cause of sudden cardiac death in young individuals. Molecular mechanisms underlying this disorder are largely unknown; this study aims at revealing how disruptions in actin-myosin interactions can play a role in this disorder. Cross-bridge (XB) kinetics and the degree of order were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…6 B ; Huang et al, 2014 ). Previous work in this model also found an increase in the rate of cross-bridge binding to thin filaments and the rate of execution of the power stroke in contracting myofibrils from ex vivo left ventricles of Tg K104E mice ( Duggal et al, 2015 ). Purified myosin from this tissue also revealed a slightly slower second-order ATP-binding constant for Tg K104E compared with Tg WT myosin ( Duggal et al, 2015 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…6 B ; Huang et al, 2014 ). Previous work in this model also found an increase in the rate of cross-bridge binding to thin filaments and the rate of execution of the power stroke in contracting myofibrils from ex vivo left ventricles of Tg K104E mice ( Duggal et al, 2015 ). Purified myosin from this tissue also revealed a slightly slower second-order ATP-binding constant for Tg K104E compared with Tg WT myosin ( Duggal et al, 2015 ).…”
Section: Discussionsupporting
confidence: 56%
“…Previous work in this model also found an increase in the rate of cross-bridge binding to thin filaments and the rate of execution of the power stroke in contracting myofibrils from ex vivo left ventricles of Tg K104E mice ( Duggal et al, 2015 ). Purified myosin from this tissue also revealed a slightly slower second-order ATP-binding constant for Tg K104E compared with Tg WT myosin ( Duggal et al, 2015 ). Collectively, these findings in full-length α-cardiac myosin are contrary to those we observed in M2β-S1, supporting the notion that the effects of the mutation on intrinsic motor properties may be dependent on the length or isoform of the myosin backbone.…”
Section: Discussionsupporting
confidence: 56%
“…Following labeling of recombinant peptide with SeTau-647 Maleimide, 5 nM of this protein was exchanged with the native LC of ventricular myosin in the exchange solution containing 15 mM KCl, 5 mM EDTA, 5 mM DTT, 10 mM KH 2 PO 4 , 5 mM ATP, 1 mM TFP, and 10 mM imidazole, pH 7 (Duggal et al, 2015 ; Huang et al, 2015 ). The reaction was allowed to occur at 30°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The K104E mutation increased the rate of XB binding to thin filaments and the rate of execution of the power stroke. Stopped-flow experiments revealed a significantly faster dissociation rate observed in Tg-K104E vs. Tg-wild-type (WT) myosin and a smaller second-order ATPbinding rate for the K104E compared with WT myosin 21 . Barth et al reported a new skeletal muscle fiber type-I myopathy in three unrelated Dutch families with progressive cardiomyopathy and early infant deaths due to cardiac failure 11 , and the genetic cause was only recently identified by Wetermen et al to be a homozygous mutation in the last acceptor splice site of the myosin regulatory light chain 2 gene which results in use of a cryptic splice site upstream of the last exon causing a frameshift and replacement of the last 32 codons by 20 different codons 129 (Fig.…”
Section: Lys104glu (K104e)mentioning
confidence: 98%